2018
DOI: 10.1016/j.apsusc.2018.05.134
|View full text |Cite
|
Sign up to set email alerts
|

Control of YH3 formation and stability via hydrogen surface adsorption and desorption

Abstract: Yttrium is known to form two hydrides: YH 2 , a metal, and YH 3 , which is dielectric. However, the stability of YH 3 is not fully understood, especially in the context of thin films, where the yttrium layer must be coated to protect it from oxidation. In this work, we show that the stability of a YH 3 thin film depends on the capping layer material. Our investigation reveals that YH 3 appears to be stabilized by hydrogen that is adsorbed to the capping layer surface. This is evidenced by the YH 3-YH 2 transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…A similar site-blocking effect has been proposed to explain the retarded dissociation of YH 3 under a Ru film. 17 Soroka et al observed that the unavailability of surface sites prevented the escape of hydrogen. By raising the temperature of the sample above the desorption temperature, the hydrogen atoms released from the YH 3 layer were able to diffuse to the surface much more rapidly, allowing the decomposition of the yttrium trihydride to proceed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar site-blocking effect has been proposed to explain the retarded dissociation of YH 3 under a Ru film. 17 Soroka et al observed that the unavailability of surface sites prevented the escape of hydrogen. By raising the temperature of the sample above the desorption temperature, the hydrogen atoms released from the YH 3 layer were able to diffuse to the surface much more rapidly, allowing the decomposition of the yttrium trihydride to proceed.…”
Section: Discussionmentioning
confidence: 99%
“…Livshits et al 14 Carbon impurities in a hydrogen plasma were found to increase blistering in tungsten targets. 15 A palladium-gold alloy was shown to accumulate hydrogen in the near-surface region when the hydrogen exit path was affected by adsorbed CO. 16 This effect also occurs without impurities; Soroka et al 17 proposed that the saturation of a ruthenium thin-film surface with hydrogen inhibits hydrogen removal from the underlying yttrium hydride layer. In all these cases, the exit of hydrogen from the bulk metal is impeded by conditions on the surface which cause reduced bulk-to-surface diffusion, recombination, and desorption.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated that the light element riched metallic solids at high pressure possess promising high-Tc phonon-mediated superconductivity due to the high Debye temperature and strong electron-phonon coupling, such as the H-riched materials (Kim et al, 2010;Errea et al, 2016;Zhong et al, 2016). H-rich materials have been considered as a potential superconductor at high pressure (Ashcroft, 2004;Wang H. et al, 2012) because they can become metallic and superconducting at much lower pressure than hydrogen due to "chemical compression" (Soroka et al, 2018). Extensive explorations of the superconducting high pressure phase diagrams of rare earth (Sc, Y, La, Ce, Pr, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, due to the change of the valence electronic state of Y atom under high pressure, there is more possibility of bonding between Y atom and H atom (Heil et al, 2019). Among these different yttrium hydrides, YH 3 allotropes provides a broad platform for the study of the structural behavior and pressure tunable thermal properties Soroka et al, 2018;Grishakov et al, 2019). For example, YH 3 is insulating in nature at ambient pressure (0 GPa) (Jarosik et al, 2017), while the insulator to superconductor transition in YH 3 occurs at pressure around 20 GPa (Kim et al, 2009;Kim et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…If we assume that transport along grain boundaries is the dominating diffusion mechanism, this justifies the usage of CPd H /dRu as approximation of the concentration gradient over the diffusion pathways through the Ru film. It has been demonstrated that our 7 nm Ru films are above the threshold thickness for polycrystalline growth [40,41]. We therefore expect that diffusion will be dominated by hopping between defects or transport along grain boundaries.…”
Section: Diffusion Coefficient Of Hydrogen In Rumentioning
confidence: 84%